Pengembangan Modul Pembelajaran Biologi Bernuansa Emotional Spiritual Quotient (ESQ) pada Materi Sistem Koordinasi untuk Siswa Kelas XI - Ambri, Ghea Nada Ufa Ariij; Arsih, Fitri (Lembaga Yasin AlSys, 2023)
So far, education in schools has focused on developing intellectual intelligence (IQ), but has not touched much on emotional intelligence (EQ) and spiritual (SQ). When these three aspects develop in learning, educational outcomes will be more optimal. Therefore, research was carried out with the aim of producing an ESQ nuanced module on the coordination system material for class XI SMA/MA students. This research is a development research using three stages of the four 4-D (four-D) models which consist of defining, designing, and developing stages. The research subjects consisted of 2 Biology lecturers at FMIPA UNP, 1 teacher and 30 students of class XI IPA at SMA Negeri 1 Sungai Limau. The research data is primary data obtained from validity and practicality questionnaires, then analyzed by descriptive analysis. From the results of the validity test, an average value of 86.30% was obtained with valid criteria, and the results of the practicality test by the teacher obtained an average value of 92.08% with very practical criteria, and the results of the practicality test by students obtained an average value of 92, 50% with very practical criteria. Thus it can be concluded that the ESQ nuanced module on the coordination system material for class XI SMA/MA students has valid and very practical criteria.